The Credit Line Channel - GREENWALD, DANIEL L.; KRAINER, JOHN; PAUL, PASCAL (Journal of Finance, 2025)
ABSTRACT Aggregate U.S. bank lending to firms expanded following the outbreak of COVID‐19. Using loan‐level supervisory data, we show that this expansion was driven by draws on credit lines by large firms. Banks that experienced larger credit line drawdowns restricted term lending more, crowding out credit to smaller firms, which reacted by reducing investment. A structural model calibrated to match our empirical results shows that while credit lines increase total bank credit in bad times, they redistribute credit from firms with high propensities to invest to firms with low propensities to invest, exacerbating the decrease in aggregate investment.